Genetic and serum biomarkers of NSAID hypersensitivity reactions - Amo, G.; García-Menaya, J. M.; Martí, M.; Gómez-Tabales, J.; Cornejo-García, J. A.; Blanca-López, N.; Canto, G.; Doña, I.; Blanca, M.; Torres, M. J.; Agúndez, J. A. G.; García-Martín, E.; et al. (Frontiers in Pharmacology, 2025)
BackgroundHypersensitivity reactions (HRs) to non-steroidal anti-inflammatory drugs (NSAIDs) constitute a significant clinical concern due to their frequency and possible severity. These reactions may involve specific immunological pathways, including activation of the high-affinity IgE receptor, or non-immunological mechanisms that result in similar clinical manifestations. Additionally, vitamin D plays an important role in the regulation of the immune response and therefore may be relevant to the development or progression of HRs to NSAIDs.MethodsTo identify new single nucleotide variants (SNVs) associated with HRs, we analyzed the exonic regions and the 3’UTR of sixteen genes related to the vitamin D pathway and the high-affinity IgE receptor, namely, FCER1A, MS4A2, FCER1G, VDR, GC, CYP2R1, CYP27A1, CYP27B1, CYP24A1, RXRA, RXRB, RXRG, IL4, IL4R, IL13, and IL13RA1 in a cohort of 1,962 participants, including 982 patients with HRs to NSAIDs and 980 controls. Additionally, serum levels of vitamin D and IgE were measured in these participants.ResultsWe identified 216 variants located in the exonic and 3′regions of these genes, 186 of which were novel. Multinomial analyses identified associations between patients with single NSAID induced urticaria/angioedema or anaphylaxis (SNIUAA) and SNVs in genes related to vitamin D (VDR rs78783628, rs739837, rs731236; CYP24A1 rs2762934). In contrast, among cross-reactive (CR) NSAIDs HRs patients, none of analyzed SNVs remained statistically significant after adjustment for multiple comparisons. Notably, the FCER1G rs11421 variant was associated with an increased risk of anaphylaxis in CR NSAIDs HRs patients. Furthermore, no statistically significant differences in serum IgE levels were observed between SNIUAA and CR NSAIDs HRs patients. However, a haplotype comprising SNVs in the RXRB gene was significantly associated with elevated serum IgE level in both patient groups. Conversely, SNIUAA patients exhibited significantly higher mean vitamin D levels compared to CR NSAIDs HRs patients and non atopic controls.ConclusionOur study highlights a significant association between SNVs in genes related to the vitamin D pathway, retinoid receptors and the high-affinity IgE receptor with the risk of NSAIDs HRs. Additionally, the correlation between IgE levels and clinical phenotypes suggests a potential role for this biomarker in the pathophysiology and stratification of these reactions.